Letter: chronic HDV infection—is ignorance bliss? Authors' reply. Issue 3 (15th January 2023) - Jachs, Mathias; Reiberger, Thomas; Ferenci, Peter
LINKED CONTENT: This article is linked to Jachs et al papers. To view these articles, visit https://doi.org/10.1111/apt.16945 and https://doi.org/10.1111/apt.17291